25-OR: Acid–Base Changes during Diabetic Ketoacidosis (DKA) in T1DM with and without SGLT2 Inhibitor (SGLT2i) - MURSIC, INES; SVEHLIKOVA, EVA; REGITTNIG, WERNER; AUGUSTIN, THOMAS; MAGNES, CHRISTOPH; EBERL, ANITA; HEISE, TIM; KLEIN, OLIVER; WOLF, MICHAEL; URSCHITZ, MARTINA; BRUNNER, MARTINA; SOURIJ, HARALD; et al. (Diabetes (New York, N.Y.), 2020)
Objectives: To evaluate the effect of SGLT2i on the development of DKA during insulin depletion in T1DM. Methods: Sixteen male, C-peptide negative T1DM subjects were enrolled in this open, randomized, crossover, bicentric trial with two 7-day treatment periods (with/without SGLT2i). At the end of each treatment period, insulin was withdrawn for a maximum of 12h, followed by recovery phase (12h). Results: SGLT2i led to significantly lower plasma glucose (PG) values during insulin depletion (PGmax with/without SGLT2i: 174±40 (mean±SD) vs. 302±48 mg/dL; 95% CI for ratio: 0.51-0.60), but to higher beta-hydroxybutyrate (BHB) values (Figure) and a steeper BHB increase (delta BHB: 8.1±2.0 vs. 6.0±1.7 µmol/L/min; 95% CI for ratio: 1.22-1.49). pH, bicarbonate and base excess during insulin depletion were comparable. Baseline glucagon (7.8±2.5 vs. 5.0±1.6 pmol/L; 95% CI for ratio: 1.26-1.95) and FFA levels (0.65±0.27 vs. 0.43±0.31 mmol/L; 95% CI for ratio: 1.08-2.28) were higher with SGLT2i, but data indicate that after increase during insulin depletion comparable concentrations were reached for both. Conclusions: SGLT2i keeps PG in near normal ranges during DKA development and recovery, potentially impeding DKA diagnosis. While SGLT2i leads to higher ketone levels, increased baseline glucagon and FFA, an effect on pH and acidosis was not demonstrated.